Effects of Oil Modification on Aging Characteristics of Asphalt Materials - Sylla, Ryan (My University, 2016)
Thermal induced cracking of asphalt mixtures is currently recognized as one of the primary distresses of asphalt pavements in cold climate regions. Thermal cracking is caused by cold temperatures, which results in the asphalt mixture becoming brittle and less capable of tolerating and relaxing thermally induced stresses. The contraction of the asphalt pavement due to decreasing temperature combined with the underlying base restraining any movement causes stress build up in the pavement until the ultimate strength is reached of the asphalt mixture, which leads to thermal crack formation. Although there are many proven asphalt modification methods to improve the asphalt performance at high service temperatures, oil modification is one of few methods that can address the low temperature distresses. Although the use of oil modifiers is common in today’s asphalt industry, oil modification’s effects to the aging mechanisms of the asphalt is relatively unknown. This study focuses on determining the implications on the aging process when using oil modifiers in asphalt binder and asphalt mastic phases. In this thesis three different oils (paraffinic, refined waste, and bio oil) were evaluated for their effects to the aging mechanisms in comparison with the unmodified base binder. The characterization of these materials was conducted by two approaches including: a.) Superpave linear viscoelastic approach using the Bending Beam Rheometer (BBR) and b.) Fracture mechanics approach using the Single Edge Notched Beam (SENB) test. In order to capture the effects of aging, the relative changes in performance were monitored through three stages of aging that aim to simulate the asphalt binder at different times within a pavement’s service life. The aging behavior of oil modified binders was also captured in the mastic phase, which is a more representative state of the continuous phase in an asphalt pavement in comparison to just the binder phase. Results indicate that the oil modification significantly effects the binder phase, but does not significantly affect the mastic phase. Binder results indicate the overall aging resistance of asphalt binder is slightly improved with oil modification and the time that aging occurs within the aging cycle is significantly altered in comparison with the unmodified binder. However, the refined waste oil in higher concentrations demonstrated detrimental effects to the aging characteristics of the binder. Mastic performance results showed little correlation with the binder performance indicating that the filler is a dominating factor. However, the mineral filler type (granite vs limestone) noticeably influenced the resulting performance of the mastics. Overall, this study concludes that oil modification can significantly alter the aging mechanisms of the binder, however these changes in binder performance do not correlate well to performance in the mixture phase.